Psychotropic medications: a descriptive study of prescription trends in Tabriz, Iran, 2021–2022 - Mostafa Farahbakhsh; Ali Fakhari; Ali Azimian; Amin Khameneh; Mahsa Matinkia; Ehsan Aghajani (BMC Psychiatry)
Abstract Introduction Mental disorders, such as anxiety and depression, significantly impacted global populations in 2019 and 2020, with COVID-19 causing a surge in prevalence. They affect 13.4% of the people worldwide, and 21% of Iranians have experienced them. Prescription analysis is critical for evaluating and improving medical care in a cost-effective manner. This study examined prescription patterns for psychotropic drugs in outpatient settings to improve the understanding of medication utilization in a variety of patients. It aimed to assist healthcare professionals in making well-informed decisions about drug prescriptions, a topic not much addressed in Iran. Method A descriptive study was conducted using data extracted from the Social Security Organization in Iran. We analyzed prescriptions in Tabriz from March 2021 to March 2022. Prescription data were categorized by medication category, physician specialty, age group, and sex. Then statistical analysis was performed using SPSS 2022. Results We analyzed the number of psychotropic medication prescriptions issued by 7246 doctors to a group of 413,466 individuals over a year representing 44.9% of our target population. The average age of individuals receiving psychotropic drugs was 45.57 years. Gabapentin had the highest prescription rate, followed by sertraline. Antidepressants accounted for 38.1% of all prescriptions, with anxiolytics accounting for 18.6%. Other psychotropic drugs included alprazolam, chlordiazepoxide, and valproate. Adults in all age groups had the highest frequency of prescriptions for psychotropic medications. The majority of patients were female (63.5%). General practitioners had the highest number of instances of prescribing psychotropic drugs, with psychiatrists contributing 54.7% of the total prescriptions. Conclusion Approximately 45% of the target population received psychotropic medication, which highlights the significant prevalence of mental health issues in Iran. Antidepressants were the most commonly administered class, highlighting the need for training programs that specifically address their possible negative effects and the correct dosage. The goal is to provide healthcare practitioners with a comprehensive understanding of prescription trends, enabling them to administer the most appropriate treatments.